Developing a Competency Assessment Model for Graduates in the Field of Information and Communication Technology of Vocational High School Expertise in North Sulawesi Province - Liando, Olivia E S; Sumual, Herry; Wullur, Mozes M.; Lengkong , Jeffry Sony Junus; Umbase, Ruth; Lumapow, Harol R.; Palilingan, Ronny; Parinsi, Mario Tulenan (International Journal of Information Technology and Education, 2025)
This study aims to develop a system-based assessment model for SMK graduates in ICT that is adjusted to the industrial occupation map. Specific objectives include: (1) designing a system-based assessment model, (2) determining the level of model feasibility, and (3) testing the usability of the assessment model. This study uses a development method (research and development) with the Design Science Research Methodology (DSRM) approach. The research procedure consists of four stages: needs analysis, system design, system creation, and evaluation and testing of the assessment model. Data collection techniques are carried out through observation, interviews, documentation studies, and the distribution of USE questionnaires for usability testing. The study results indicate that the developed assessment model has met the feasibility aspects based on expert assessment and has a high level of usability, ease of use, and user satisfaction, as indicated by the test results using the USE Questionnaire. This model is also able to map graduate competencies based on industry needs more accurately and objectively. In conclusion, the developed system-based competency assessment model has proven to be feasible and effective in measuring and mapping the competencies of vocational high school graduates in the field of ICT according to the needs of the world of work. The implementation of this model is expected to increase the competitiveness of vocational high school graduates and strengthen the quality of vocational education in Indonesia.